Virulence factors of bovine mastitis pathogens: distribution, pathogenesis, and emerging vaccines targeting virulence factors: a literature review - Li, Hao; Wang, Ziyan; Barkema, Herman W.; Li, Xiaohan; Song, Deyuan; Ren, Meiyi; Tong, Jingdi; Liu, Mingchao; Gao, Jian; Cheng, Jia (Frontiers in Veterinary Science, 2026)
Bovine mastitis, mainly caused by contagious pathogens like Staphylococcus aureus, Streptococcus agalactiae, and Mycoplasma bovis, environmental pathogens such as Escherichia coli, Streptococcus uberis, Klebsiella pneumoniae, and a more opportunistic pathogen like Streptococcus dysgalactiae, severely threatens dairy production. These mastitis pathogens rely on their respective virulence characteristics to exert different inflammation of the mammary gland. Meanwhile, antimicrobials remain the primary treatment for bovine mastitis, but growing resistance often causes failure. Therapeutic approaches targeting the virulence factors utilized by these mastitis-causing pathogens are expected to become effective alternatives to antimicrobial therapy in dairy farming. Therefore, the objective of this review is to investigate the prevalence and pathogenic roles of virulence genes in mastitis pathogens, with an extensive exploration of the emerging vaccination approaches targeting the virulence factors for safeguarding dairy animal health.